DEVELOPMENT PCR TEST SYSTEM FOR SPECIFIC DETECTION OF BACTERIA BABESIOSIS ANIMALS - Грубіч, П. Ю.; Курман, А. Ф.; Лепета, Л. В.; Пархоменко, Є. А. (Scientific Progress & Innovations, 2013)
The system of oligonucleotide primers that allow PCR amplified in section 18S rRNA gene 6 species of the genus Babesia. The article presents the features and design of primers tested multiplexed PCR test systems for the identification of the genus Babesia. Yznacheni in amplified fragment length - From 299 to 2 5 8 pairs for Babesia canis, Babesia divergens, Babesia caballi, Babesia major, Babesia bovis. Studied 342 blood samples from different animal species and is 100% coincidence with the results of microscopic studies.